Decrease of Anticholinergic Drug Use in Nursing Home Residents in the United States, 2009 to 2017. Issue 12 (15th August 2020) - Malagaris, Ioannis; Mehta, Hemalkumar B.; Li, Shuang; Goodwin, James S.
Abstract : OBJECTIVE: To investigate the time course of anticholinergic drug use in nursing home residents and assess if any temporal change in anticholinergic use varied by nursing home quality rating. DESIGN: Retrospective repeated cross‐sectional analysis of Medicare enrollment, Parts A, B, and D, claims data linked to the Minimum Data Set from 2009 to 2017. SETTING: Medicare‐certified nursing homes. PARTICIPANTS: Long‐term residents 65 years or older with nursing home stay of at least 100 consecutive days within a given calendar year. MEASUREMENTS: Estimates of anticholinergic drug prescription rates between 2009 and 2017 were based on a binary variable indicating whether a resident received a drug with high anticholinergic activity, as defined by the Anticholinergic Cognitive Burden scale, for at least 1 day during the initial 100 consecutive days of nursing home stay in a given calendar year. We used mixed effects logistic regression models to determine adjusted rates of anticholinergic use each year and test the interaction between nursing home quality rating and year, while adjusting for patient and nursing home characteristics. RESULTS: The cohort included 786, 858 100‐day nursing home stays (299, 354 unique residents) in 6, 703 nursing homes for the years 2009 to 2017. Prescription rates were stable at approximately 34% to 35% between 2009 and 2011, then gradually decreased to 24.3% in 2017 ( P < .0001), with the decline being more pronounced in nursing homes having high quality ratings ( P < .0001). Rates for anticholinergic drugs in nursing homes with 4 to 5 star quality rating (33.7% in 2011 to 23.3% in 2017) showed a steeper decline over time relative to nursing homes with 1 to 2 star quality rating (34.2% in 2011 to 25.2% in 2017) ( P < .0001). CONCLUSIONS: The use of drugs with high anticholinergic activity has declined from 2009 to 2017, with a greater decline in higher‐quality nursing homes.